A Community Guide to Urban Forest Inventories - Francisco J. Escobedo; Michael G. Andreu (EDIS)
FOR-173, a 4-page fact sheet by Francisco Escobedo and Michael Andreu, defines what an urban forest inventory is and its advantages, what the conditions for conducting and funding and inventory should be, and some management options. Includes references. Published by the UF School of Forest Resources and Conservation, January 2008.